2019
DOI: 10.1038/s41598-019-48880-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response against koala retrovirus (KoRV) in koalas harboring KoRV-A in the presence or absence of KoRV-B

Abstract: Koala retrovirus (KoRV) is in the process of endogenization into the koala ( Phascolarctos cinereus ) genome and is currently spreading through the Australian koala population. Understanding how the koala’s immune system responds to KoRV infection is critical for developing an efficacious vaccine to protect koalas. To this end, we analyzed the antibody response of 235 wild koalas, sampled longitudinally over a four-year period, that harbored KoRV-A, and with or without KoRV-B. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Ten captive northern koalas (endogenously infected with KoRV-A) were vaccinated subcutaneously with two doses of the vaccine. Prior to vaccination, we detected anti-KoRV IgG titres that were similar to levels previously reported in wild koalas harbouring endogenous KoRV 14 . Following vaccination, all animals had significant increases in total anti-KoRV IgG levels, ranging from a 2–37 fold increase by week 8 (Fig.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Ten captive northern koalas (endogenously infected with KoRV-A) were vaccinated subcutaneously with two doses of the vaccine. Prior to vaccination, we detected anti-KoRV IgG titres that were similar to levels previously reported in wild koalas harbouring endogenous KoRV 14 . Following vaccination, all animals had significant increases in total anti-KoRV IgG levels, ranging from a 2–37 fold increase by week 8 (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Recent studies suggest that KoRV-A sits at an intersection between a fully endogenized retrovirus and an exogenous retrovirus through its ability to produce infectious particles in the koala 19 . KoRV-A-directed immune response in natural infection has also been previously established, thus confirming the possibility for vaccine development 14 . Similar to observations from our current study, ongoing studies in humans have shown that HERV-K-directed immune responses can serve as a basis for vaccine development against HERV-K-associated cancers 20 , 21 .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In a study with 16 koalas, Fiebig et al observed that koalas did not produce antibodies against KoRV-A [55], but in a recent study using 235 koalas, Quigley et al analyzed the antibody response and found that most koalas produced anti-KoRV antibodies [56]. This finding is very important for developing a therapeutic KoRV vaccine.…”
Section: Immune Response Against Korv Infection In Koalasmentioning
confidence: 99%